Kepemimpinan Transformasional Yang Melayani Masyarakat Dalam Bingkai Kebhinekaan - Agung Priambodo, Ervin (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
Diversity is a gift from the almighty power of the Indonesian people that cannot be denied anymore, which is a form of national strength and noble values possessed by the Indonesian people. Diversity is a spirit in providing good services for all Indonesian citizens who do not look at ethnic origin, skin color, groups and groups. Transformational leadership is a leadership style used by a leader if he wants a group to widen its boundaries and have performance beyond the status quo or achieve a whole new set of organizational goals. Transformational leadership is the answer in providing excellent service quality for all people in the scope of government. The leadership of transformation that provides quality of service within the frame of diversity will satisfy the community so that it will usher in the corridor of the Unitary Republic of Indonesia. DAFTAR PUSTAKA Buku-Buku Brundet, Mark, Neil Burton, Robert Smith, Leadership in Education, London : Sage Publish, 2003. Cassidy, Carlene M, Robert Kreitner, Principles of Management 12th, USA :SouthWestern Cengage Learning, 2011. Daft, Richard L, The Leadership Experience 6th, USA : Cengage Learning, 2015. Gibson, Organizations, New York : McGraw-Hill Companies, Inc, 2006. Hamengku Bowono X, Sultan, Merajut Kembali Ke indonesiaan Kita, Jakarta :Gramedia Pustaka Utama, 2008. Hill, Arthur V, Field Service Management, America : RICHARD D. IRWIN, INC,1992. Hughes, Bass, Leadership Enchanging The Lessons of Experience 8th, New York :McGraw Hill, 2015. Jason A. Colquit, Jeffery A. Lepine and Michael J. Wesson, Organizational Behavior: Improving Perfor mance and Commitment in the Workplace, Bston: McGraw-Hill, 2011. Kaelan, Pendidikan Pancasila, Yogyakarta :Paradigma, 2004. Kasmir, Customers Services Excellent, Jakarta :Raja Grafindo, 2017. Majid, Suharto Abdul, Customer Dalam Bisnis Jasa Transportasi, RAJA WALI PERS:PT. Raja Grafindo, 2012. Malau, Harman, Manajemen Pemasaran, Bandung : Alfabeta, 2017. Nelson, Debra L., James Campbell Quick, Organizational Behavior: Foundation, Realities and Chalenge,Canada:Thomson, 2006. Palmer, Andrian, Principles Of Services Marketing, Singapore : McGraw-Hill, 2001. Rangkuti, Freddy, Customer Service Satisfaction & Call Center, Jakarta :PT. Gramedia Pustaka Utama, 2014. Customer Care Excellence, Jakarta :Gramedia Pustaka Utama, 2016. Robert, Lussier N, Achua, Management Fundamentals, Concept, Aplications, Skill Development, Australia: South Western, 2010. Scermerhorn, John R. Jr, Daniel G. Bachrach, Introduction to Management 13th, Singapore : Wiley, 2015. Wibowo, Manajemen Kinerja, Jakarta : PT. Raja Grafindo Persada, 2014. Yukl, Gary A, Leadership in Organizations 8t, New England : Pearson, 2013. Jurnal Gao-Liang Wang, Yu-Je Lee, Song-Fen Cheng, The Impact of Organizational Climate, Service Quality and customer Satisfaction on Organizational Performance: a Case of International Tourist Hotel Industry in Taipei City,International Journal of Business and Management Invention., Volume 5 Issue 6 ||June. 2016 ||., h. 58 Roland K. Yeo, Servicing service quality in higher education: quest for excellence, VOL. 16 NO. 3 2008, Q Emerald Group Publishing Limited, ISSN 1074-8121, h. 100. Internet http://www.astalog.com/974/asal-mula-terbentuknya-bhineka-tunggal-ika.htm http://www.beraunews.com/serba-serbi/3052-melayani-masyarakat-mulailah-dari-yang-sederhana https://damainegerikutercinta.wordpress.com/2012/05/14/kita-butuh-pemimpin-yang-amanah-dan-menjaga-kebhinekaan-5/ https://dkn.go.id/ruang-opini/9/jumlah-pulau-di-indonesia.htm. http://jateng.tribunnews.com/2016/09/01/data-terkini-jumlah-penduduk-indonesia-2579-juta-yang-wajib-ktp-1825-juta. https://www.bps.go.id/KegiatanLain/view/id/127).